2008
DOI: 10.1021/cm800247u
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Materials with the Na0.44MnO2 Structure: Effect of Titanium Substitution on Physical and Electrochemical Properties

Abstract: Partial titanium substitution of electrodes with the Na 0. 44

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
37
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…11,12 A series of titanium-substituted Na 0.44 MnO 2 and Li 0.44 MnO 2 materials, in which Ti 4+ partially occupies MO 6 polyhedra, have also been reported as positive electrodes for sodium and lithium-ion batteries. 10 Doping with titanium increases the unit cell size and in the case of lithiated materials, raises the potential of lithium intercalation/deintercalation 13 and leads to higher capacities. For instance, Li x Ti 0.22 Mn 0.78 O 2 is reported to deliver about 10-20% more capacity than Li x MnO 2 .…”
mentioning
confidence: 99%
“…11,12 A series of titanium-substituted Na 0.44 MnO 2 and Li 0.44 MnO 2 materials, in which Ti 4+ partially occupies MO 6 polyhedra, have also been reported as positive electrodes for sodium and lithium-ion batteries. 10 Doping with titanium increases the unit cell size and in the case of lithiated materials, raises the potential of lithium intercalation/deintercalation 13 and leads to higher capacities. For instance, Li x Ti 0.22 Mn 0.78 O 2 is reported to deliver about 10-20% more capacity than Li x MnO 2 .…”
mentioning
confidence: 99%
“…Various Na-Mn oxides such as NaMn 1/3 Ni 1/3 Co 1/3 PO 4 [6], Na x Mn 5 O 10 [7], Na 2 Mn 5 O 10 [8], and Na 4 Mn 9 O 18 have been extensively researched as active materials in SIB systems due to the presence of the extensive channels for Na ion intercalation and deintercalation [9]. Among them, Na 4 Mn 9 O 18 exhibits the MnO 6 octahedra and MnO 5 square cone, which are able to constitute the wide S-type double tunnels for Na ion diffusion [10]. Whitacre et al reported the Na 4 Mn 9 O 18 as a positive electrode material for an aqueous sodium ion battery (ASIB), and this material cathode displayed a capacity of 45 mAh·g −1 at a current density of C/8 rate [11].…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3,4,5 However, a significant portion of the capacity lies above 4.4 V vs. Li/Li + , limiting the energy density attainable with conventional electrolytes. 6 Above 4.2 V a substantial increase of interfacial impedance has been reported that results in considerable power loss and arises from the formation of surface films due to electrolyte oxidation and LiPF 6 decomposition.…”
Section: Introductionmentioning
confidence: 99%